Looking Back at the Audience: The RSC & The Wooster Group’s "Troilus and Cressida" (2012) - Mancewicz, Aneta (Multicultural Shakespeare: Translation, Appropriation and Performance, 2014)
The controversy around the RSC & The Wooster Group’s Troilus and Cressida (Stratford-upon-Avon 2012) among the spectators and critics in Britain revealed significant differences between the UK and the US patterns of staging, spectating, and reviewing Shakespeare. The production has also exposed the gap between mainstream and avant-garde performance practices in terms of artists’ assumptions and audiences’ expectations. Reviews and blog entries written by scholars, critics, practitioners, and anonymous theatre goers were particularly disapproving of The Wooster Group’s experimentation with language, non-psychological acting, the appropriation of Native American customs, and the overall approach to the play and the very process of stage production. These points of criticism have suggested a clear perception of a successful Shakespeare production in the mainstream British theatre: a staging that approaches the text as an autonomous universe guided by realistic rules, psychological principles, and immediate political concerns. If we assume, however, that Troilus and Cressida as a play relies on the dramaturgy of cultural differences and that it consciously reflects on the notion of spectatorship, the production’s transgression of mainstream patterns of staging and spectating brings it surprisingly close to the Shakespearean source.